Community, Engagement and Connectedness : Reflections on Pathway Programs at a Regional Australian University. - Spence, Jenny; Davis, Charmaine; Green, Jonathan H.; Green, Orié; Harmes, Marcus; Sherwood, Celeste (Student Success v.13 n.3 p.11-19 https://doi.org/10.5204/ssj.2441, 2022)
The progressive democratisation of Australian higher education has numerous causes including the increase in the number of universities and therefore university places across the later 20th and into the 21st century, as well as initiatives by governments of different ideological hues to increase the total percentage of the population with a university degree. This latter impulse, in particular, has increased significantly the number of students entering university via pathway programs, meaning programs which provide the opportunity to undertake study to inculcate university-standard skills and enable matriculation into university for people who are otherwise ineligible. The students in pathway programs are sometimes disengaged from learning, coming from so-called non-traditional pathways that may signify a disconnect between them and their institutions of learning. This practice report, therefore, examines efforts to address “connectedness” in pathway programs at a regional university in Australia. The pathway programs at UniSQ College are underpinned by an inclusive and holistic teaching philosophy that supports students’ access to higher education. Through the lenses of social, emotional, cognitive, behavioural, and collaborative engagement, practitioners examined and reflected on ways in which this philosophy was embedded in the day-to-day work of UniSQ College through deliberate efforts to promote and maintain connectedness. By reflecting on and articulating these connections, we have provided a base for developing a future evaluative framework that will critically examine the extent to which our practices, through student engagement, foster connectedness. [Author abstract]